Research progress on the current status and influencing factors of road traffic injuries among online delivery drivers - Rusi YANG; Juan SONG; Ming HU (Editorial Office of Chinese Journal of Public Health, 2024)
In recent years, with the continuous development of the take-out industry, the traffic accidents involving online delivery drivers have been frequent, posing a major threat to road traffic safety. However, there are few studies on road traffic injuries (RTIs) among online delivery drivers. Online delivery drivers use electric bikes as their main mode of transportation, and their driving behavior is significantly different from that of ordinary cyclists. There are multiple and complex influencing factors that contribute to road traffic injuries. This paper providesd an overview of the research on road traffic injuries among online delivery drivers in terms of individual factors, vehicle factors, road factors, environmental factors, and management factors, while also describing the current situation of road traffic injuries among online delivery drivers both domestically and internationally. It aims to serve as a reference for reducing traffic injuries among online delivery drivers and improving road traffic safety.